Rumination, intolerance of uncertainty and paranoia in treatment resistant psychosis. Issue 1 (2nd January 2021) - Lebert, L.; Turkington, D.; Freeston, M.; Dudley, R.
ABSTRACT: Background: This study explored the relationship between depressive rumination, non-depressive rumination, intolerance of uncertainty (IU) and paranoia. Method: Using a single group design, the relationship between rumination, IU, depression, positive symptoms of psychosis and paranoia was studied in 24 participants with treatment resistant psychosis. Results: Non-depressive rumination demonstrated a specific relationship with paranoia, but not with delusions or positive symptoms generally. Moreover, paranoia was strongly associated with IU. Conclusions: Rumination and IU may contribute to the maintenance of paranoid thinking and may be important in the treatment of paranoia and persecutory ideation.